New Type of Capacitive Detector for Determination of Ions - Samphao, Anchalee; Svegl, Franc; Kalcher, Kurt (Asian Journal of Chemistry, 2011)
A new type of capacitive detector for the determination of ions was designed and fabricated. It consists of two thin layers of gold (thickness 24 nm) sputtered on a glass membrane (20 mm × 20 mm × 0.2 mm) as a dielectric. The upper metal layer of the capacitor had a circular gap (28 mm2) in the center as the sensing area. The capacitor was coupled with an inductor in parallel configuration to form a resonance circuit, whose frequency was determined. Solutions containing ions applied to the sensing area caused an increase in the capacitance owing to an enhanced charge density on the sensing area. The upper limit of detection for ions was around 10-3 mol dm-3 of monovalent cations and anions. Higher concentrations did not produce higher capacitance. The lower detection limits were around 5 × 10-5 mol dm-3. Studies were focused on the influence of the metal film thickness, size of the sensing area, response time, dynamic range, sensitivity, detection limit and long-term stability of the detector. The response was stable and reproducible for over 5 months. The signal responses were compared to conductivity measurements under flow injection conditions with standard solutions and mineral water samples. The results show a good correlation between both methods of measurement.